Travelling Virtual Balise for ETCS - Filip, Aleš (My University, 2017)
A great effort of railway industry is currently focused on exploitation of Global Navigation Satellite System (GNSS) for the European Train Control System (ETCS). It has been assessed that replacement of track balises, used for safe train location determination, with Virtual Balises (VBs) detected by means of GNSS will significantly reduce the track-side infrastructure and operational costs. However, this innovated ETCS can be put into operations only in the case when detection of VBs by means of GNSS will achieve the same Safety Integrity Level (SIL 4) and availability as it is required for physical balise groups. This paper describes a novel Travelling Virtual Balise (TVB) concept, which was proposed to meet demanding ETCS safety requirements for GNSS using the existing EGNOS Safety-of-Life (SoL) service. The TVB concept profits from the basic feature of GNSS – i.e. the ability of abundant train position determination in GNSS service volume, what cannot be realised by current track balise groups with a spacing of hundreds of meters or more. The frequent GNSS train positions are namely utilized for: 1) fast diagnostics of on-board Location Determination System (LDS), 2) introduction of reactive fail-safety into LDS, and 3) derivation and justification of the ETCS safety requirements for EGNOS. The TVB concept brings one significant advantage to ETCS in contrast to the static VBs – i.e. the safety requirement for LDS doesn’t depend longer on the distance between successive Virtual Balises. It means that the existing spacing between physical balise groups (up to 2.5 km) can be also preserved in case of TVBs. It can significantly improve the availability of LDS. Further it was found that a less demanding THR requirement for GNSS of about 1e-7 / 1 hour or more still enables to meet the ETCS THR requirement for VB determination, i.e. THRVB of 0.67e-9/ 1 hour.
Cestující virtuální balíza pro ETCS
Keywords: GPS; EGNOS; Galileo; GPS; EGNOS; Galileo